Development and adhesion characterization of a silicon wafer for temporary bonding. (April 2018) - Montméat, P.; Enot, T.; Enyedi, G.; Pellat, M.; Thooris, J.; Fournel, F.
Abstract: The development of a silicon temporary carrier for thin wafer handling for 3D applications was investigated. Process selection and optimization ended up with a silicon carrier entirely covered with an antistick layer based on a fluorinated polymer. The carrier preparation was quite easy because only one coating was used and no sticking edge zone was needed onto the carrier. The fluorinated coating led to a very hydrophobic behavior. When bonded with a thermoplastic glue, it also exhibited very antiadhesive properties because the adherence was as low as 0.4 J/m 2 and lower than the adherence of a stack without any antiadhesive layer (above 4 J/m 2 ). The carrier was nevertheless suitable for different back side processes in 300 mm: grinding, chemical cleaning, chemical mechanical polishing and silicon oxide deposition. Compared with a commercial carrier, it exhibited the same level of performance for the integration. The proposed carrier was compatible with a mechanical debonding of a thinned bonded structure with a silicon device wafer of 80 µm. The carrier recycling was possible without any new preparation.